Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

Preparation of AuSe-BNPs/CFME and its high-sensitivity simultaneous detection of caffeic acid and dihydrotanshinone I - Han Cheng; Yanbing Pan; Tao Fang; Uchkun Ishimov; Awais Ihsan; Abrar Hussain; Ruiting Tian; Wenwen Ma; Jun Li; Xianju Huang (Chemical Engineering Journal, 2025)

Foxp3 inhibits PCV2 replication by reducing the ATPase activity of Rep - Ruijiao Jiang; Qiuyan Huang; Ruiting Shen; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2025)

Halobacillus rhizosphaerae sp. nov., a moderately halophilic bacterium with protease activities isolated from the rhizosphere soil of the mangrove Acanthus ebracteatus - Doudou Yin; Junjie Xie; Rui Liu; Chaodong Song; Ying Liang; Hongzhi Huang; Yihui Huang; Ruiting Long; Naikun Shen; Bing Yan; Hongyan Zhang (Antonie van Leeuwenhoek, 2025)

Instance segmentation and stand-scale forest mapping based on UAV images derived RGB and CHM - Yunhong Xie; Yifu Wang; Zhao Sun; Ruiting Liang; Zhidan Ding; Baoying Wang; Shaodong Huang; Yujun Sun (Computers and Electronics in Agriculture, 2024)

Transcriptome and small RNA analysis unveils novel insights into the C4 gene regulation in sugarcane - Xiuting Hua; Zhen Li; Meijie Dou; Yanqing Zhang; Dongxu Zhao; Huihong Shi; Yihan Li; Shuangyu Li; Yumin Huang; Yiying Qi; Baiyu Wang; Qiyun Wang; et al. (Planta, 2024)

Global meta-analysis and three-year field experiment shows that deep placement of fertilizer can enhance crop productivity and decrease gaseous nitrogen losses - Peng Wu; Qi Wu; Hua Huang; Lin Xie; Haoyuan An; Xintong Zhao; Fangtao Wang; Ziting Gao; Ruiting Zhang; Kemoh Bangura; Jianfu Xue; Min Sun; et al. (Field Crops Research, 2024)

Scrub-vegetation cover impact on soil water migration and temperature change during freeze–thaw events in sandy desert soils of northwest China - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Ruiting Jia (CATENA, 2024)

Effects of Chaihu Shugan San on Brain Functional Network Connectivity in the Hippocampus of a Perimenopausal Depression Rat Model - Ruiting Huang; Min Gong; Xue Tan; Jianying Shen; You Wu; Xiaoshi Cai; Suying Wang; Li Min; Lin Gong; Wenna Liang (Molecular Neurobiology, 2024)

An attomolar-level electrochemical DNA biosensor based on target-triggered and entropy-driven catalytic amplification integrated with AuNPs@ZIF-8 nanocomposites for oral cancer overexpressed 1 detection - Jing Li; Qi Jiang; Minhui Chen; Wei Zhang; Ruiting Liu; Jin Huang; Qin Xu (Analytica Chimica Acta, 2024)

Performance analysis of two-stage CO2 transcritical refrigeration cycles with absorption subcooling and mechanical recooling - Caoxuheng Huang; Zeyu Li; Zhihao Ye; Ruiting Wang (International Journal of Refrigeration, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Nebulization Therapy with Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes for COVID-19 Pneumonia - Meiping Chu; Hao Wang; Linjie Bian; Jiehui Huang; Danping Wu; Ruiting Zhang; Fangli Fei; Yigang Chen; Jiazeng Xia (Stem Cell Reviews and Reports, 2022)
Background Scientists have been facing numerous challenges in the development of an effective therapeutic strategy for the treatment of COVID-19 pneumonia. Several studies have suggested that improving patient immunity and reducing lung injury induced by SARS-CoV-2 may be effective for treating patients with COVID-19. Methods A pilot trial of nebulization therapy with exosomes of mesenchymal stem cells (MSCs) was performed on seven patients with COVID-19 pneumonia. Exosomes secreted from MSCs were collected and purified using multiple ultrafiltration steps. All patients were treated with nebulization of MSC-derived exosomes, and primary safety and efficacy outcomes were evaluated. Results Our clinical study demonstrated that nebulization of MSC-derived exosomes is a novel method that might be utilized in the treatment of COVID-19 pneumonia. Nebulization of MSC-derived exosomes did not induce acute allergic or secondary allergic reactions but did promote the absorption of pulmonary lesions and reduce the duration of hospitalization for mild cases of COVID-19 pneumonia. Conclusions Nebulization of MSC-derived exosomes is a safe, effective, and simple method, and their application at the beginning of treatment may be more beneficial. Trial Registration Chinese Clinical Trial Registry, ChiCTR2000030261. Registered on 26 February 2020. Graphical Abstract

White Matter Free Water is a Composite Marker of Cerebral Small Vessel Degeneration - Peiyu Huang; Ruiting Zhang; Yeerfan Jiaerken; Shuyue Wang; Hui Hong; Wenke Yu; Chunfeng Lian; Kaicheng Li; Qingze Zeng; Xiao Luo; Xinfeng Yu; Xiao Wu; et al. (Translational Stroke Research, 2022)